Weed Control in Corn (Zea mays L.) as Influenced by Preemergence Herbicides - Travis W. Janak; W. James Grichar (International Journal of Agronomy)
Field studies were conducted in central and south-central Texas from 2013 through 2015 to evaluate crop tolerance and efficacy of various preemergence herbicides alone and in combination for weed control in field corn. Acetochlor and pendimethalin alone, S-metolachlor plus mesotrione, and the three-way combination of S-metolachlor plus atrazine plus mesotrione provided the most consistent control of annual grasses including browntop panicum (Panicum fasciculatum L.), Texas millet (Urochloa texana L.), barnyardgrass (Echinochloa crus-galli L.), and sprawling signalgrass (Brachiaria reptans L.). Palmer amaranth [Amaranthus palmeri (S.) Wats.] control was at least 90% with fluthiacet-methyl plus pyroxasulfone, atrazine plus either acetochlor, alachlor, dimethenamid-P, S-metolachlor, or S-metolachlor plus mesotrione, saflufenacil plus dimethenamid-P, and S-metolachlor plus mesotrione. Hophornbeam copperleaf (Acalypha ostryifolia L.) was difficult to control; however, acetochlor, saflufenacil or pyroxasulfone alone, saflufenacil plus dimethenamid-P, and S-metolachlor plus mesotrione provided at least 90% control. Acetochlor or saflufenacil alone, thiencarbazone-methyl plus isoxaflutole, dimethenamid-P plus atrazine, rimsulfuron plus mesotrione, and saflufenacil plus dimethenamid-P controlled common sunflower (Helianthus annuus L.) at least 90%. Corn injury was minimal (≤3%) with all herbicides. In general, corn grain yield was greatest with herbicide treatments containing more than one active ingredient compared with a single active ingredient.